Predation by Misumenops pallidus (Araneae: Thomisidae) on insect pests of soybean cultures in Buenos Aires Province, Argentina - González, Alda (2009)
This study analyzes predation by adult females of Misumenops pallidus (Keyserling 1880) on pairs of prey items representing non-pest insects and potential pests. The phenology of the potential pests was such that each insect guild peaked sequentially, while non-pest herbivorous and insectivorous insects were present during the entire period. Field experiments were made in a commercial 50-ha soybean plot during two successive years. Ten cages 1 × 1 × 0.5 m were placed in peripheral furrows of a soybean commercial plot. The pest species were preyed on differentially, with the order from the most favored species to the least with respect to non-pest herbivorous and insectivorous insects was as follows: defoliating lepidopterous larvae, seed feeding pentatomids in their early nymphal instars, stem boring lepidopterous larvae, and seed feeding pentatomids in older nymphal and adult instars. Adult females of M. pallidus fed on all the insect species offered, but in the presence of defoliator larvae, they hardly accepted alternative prey, whereas in the presence of other prey, they maintained a more generalized diet.